Enhancing Innovative Work Behavior in the Public Sector Through Transformational Leadership: The Mediating Roles of Person–Organization Fit and Psychological Empowerment - Wijaya, Prakuta; Noermijati; Tri Kurniawati, Desi (Jurnal Ilmiah Administrasi Publik, 2026)
This study aims to analyze the influence of transformational leadership on innovative work behavior with person–organization fit and psychological empowerment as mediating variables among employees of the Malang Immigration Office. This research employs a quantitative approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM) and involves 132 respondents through questionnaire distribution. The results indicate that transformational leadership has a positive and significant effect on innovative work behavior, person–organization fit, and psychological empowerment. In addition, person–organization fit and psychological empowerment also have a positive and significant effect on innovative work behavior. Both variables are proven to partially mediate the relationship between transformational leadership and innovative work behavior. These findings emphasize the importance of leadership that aligns individual values with organizational values and creates a psychologically empowering work environment to encourage innovation in the public sector.